2013
DOI: 10.1136/emermed-2012-202143
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic lacerations: what are the risks for infection and has the ‘golden period’ of laceration care disappeared?

Abstract: Objective To determine risk factors associated with infection and traumatic lacerations and to see if a relationship exists between infection and time to wound closure after injury. Methods Consecutive patients presenting with traumatic lacerations at three diverse emergency departments were prospectively enrolled and 27 variables were collected at the time of treatment. Patients were followed for 30 days to determine the development of a wound infection and desire for scar revision. Results 2663 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 27 publications
0
61
1
15
Order By: Relevance
“…In this SR, 40 of the included studies were cohort studies, among which the most frequently observed RFs were age, [12][13][14][15][16][17][18][19] diabetes mellitus (DM), 15,[17][18][19][20][21] chronic obstructive pulmonary disease 13,15,19,22 and type of diagnosis (gastrointestinal, cardiovascular or trauma), [14][15][16]23 body mass index, 13,19,24 compromised immune system, 23,25,26 male sex, 20,22,27 female sex, 15,18 weight loss, 13,15 smoking, 13,15 temperature ≥38.5°C or ≤36.0°C, 28,29 medicated hypertension, 15,26 serum albumin levels (<3.0 g/dL), 12,30 and anemia. 16,24 In contrast, several studies observed a lower proportion of other intrinsic RFs ( Supplementary Table S1).…”
Section: Intrinsic Rfs For Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this SR, 40 of the included studies were cohort studies, among which the most frequently observed RFs were age, [12][13][14][15][16][17][18][19] diabetes mellitus (DM), 15,[17][18][19][20][21] chronic obstructive pulmonary disease 13,15,19,22 and type of diagnosis (gastrointestinal, cardiovascular or trauma), [14][15][16]23 body mass index, 13,19,24 compromised immune system, 23,25,26 male sex, 20,22,27 female sex, 15,18 weight loss, 13,15 smoking, 13,15 temperature ≥38.5°C or ≤36.0°C, 28,29 medicated hypertension, 15,26 serum albumin levels (<3.0 g/dL), 12,30 and anemia. 16,24 In contrast, several studies observed a lower proportion of other intrinsic RFs ( Supplementary Table S1).…”
Section: Intrinsic Rfs For Infectionmentioning
confidence: 99%
“…DM was identified in 2 studies 20,21 that have demonstrated statistically significant differences. An Italian epidemiologic surveillance program in 18 ICUs with a total sample of 5,561 patients concluded that DM is associated with twice the risk of developing an abdominal surgery-related infection and 4 times the risk of HAIs in the bloodstream.…”
Section: Intrinsic Rfs For Infectionmentioning
confidence: 99%
“…Besides, previous studies suggested that wounds on head and neck were less commonly associated with infection development than other locations. In this regard, the incidence of infection estimated 1% to 2% in head and neck, whereas legs and lower extremities were as high is 23% (34)(35)(36)(37). Since these sites are considered to be more infection-prone (20), it is therefore important to consider the site of wounds once deciding to choose cleansing agents with better efficacy and lower adverse effects.…”
Section: Discussionmentioning
confidence: 97%
“…Many individuals across the globe experience a laceration—a wound from splitting or tearing of skin. Over six million laceration treatments occur in U.S. inpatient emergency departments each year at a cost of well over $3 billion (Quinn et al., 2014). Fig.…”
Section: Introductionmentioning
confidence: 99%